Functional Rearrangement of the Light-Harvesting Antenna upon State Transitions in a Green Alga - Wlodarczyk, Lucyna M. (Biophys J, 2015)
State transitions in the green alga Chlamydomonas reinhardtii serve to balance excitation energy transfer to photosystem I (PSI) and to photosystem II (PSII) and possibly play a role as a photoprotective mechanism. Thus, light-harvesting complex II (LHCII) can switch between the photosystems consequently transferring more excitation energy to PSII (state 1) or to PSI (state 2) or can end up in LHCII-only domains. In this study, low-temperature (77 K) steady-state and time-resolved fluorescence measured on intact cells of Chlamydomonas reinhardtii shows that independently of the state excitation energy transfer from LHCII to PSI or to PSII occurs on two main timescales of <15 ps and ∼100 ps. Moreover, in state 1 almost all LHCIIs are functionally connected to PSII, whereas the transition from state 1 to a state 2 chemically locked by 0.1 M sodium fluoride leads to an almost complete functional release of LHCIIs from PSII. About 2/3 of the released LHCIIs transfer energy to PSI and ∼1/3 of the released LHCIIs form a component designated X-685 peaking at 685 nm that decays with time constants of 0.28 and 5.8 ns and does not transfer energy to PSI or to PSII. A less complete state 2 was obtained in cells incubated under anaerobic conditions without chemical locking. In this state about half of all LHCIIs remained functionally connected to PSII, whereas the remaining half became functionally connected to PSI or formed X-685 in similar amounts as with chemical locking. We demonstrate that X-685 originates from LHCII domains not connected to a photosystem and that its presence introduces a change in the interpretation of 77 K steady-state fluorescence emission measured upon state transitions in Chalamydomonas reinhardtii.